Prevention of disease caused by fluoro-edenite fibrous amphibole: the way forward - Caterina Bruno; Biagio Bruni; Salvatore Scondotto; Pietro Comba (Istituto Superiore di Sanità, 2015)
Few months after the publication of the monographic section of Annali dell'Istituto Superiore di Sanità second issue of 2014 "Health impact of fibres with fluoro-edenitic composition", the carcinogenicity of fluoro-edenite was assessed by the International Agency for Research on Cancer (IARC) in the frame of Monograph 111. The IARC Working Group concluded that there is sufficient evidence in humans that exposure to fluoroedenite fibrous amphibole causes mesothelioma, and sufficient evidence of carcinogenicity in experimental animals. Fluoro-edenite was allocated to Group 1 (the agent is carcinogenic to humans). Now, in view of the recent IARC evaluation, preventive action in Biancavilla requires an upgrade. First of all, environmental monitoring has to be further implemented. All operations of house cleaning should be performed employing wet tools, in order to avoid dust-raising. It is very important that environmental and biological monitoring be related to epidemiological surveillance. The recently approved act of the Sicilian Government concerning a plan of health interventions in Biancavilla will favour cooperation between national, regional and local health institutions with the common goal of improving the quality and appropriateness of diagnostic and therapeutics procedures offered by the health services.